Youth, Crime, and Justice : learning through cases - Gebo, Erika; Boyes-Watson, Carolyn (Lanham : Rowman & Littlefield, 2023)
"This comprehensive textbook covers the historical evolution of the core developmental institutions within modern society charged with the socialization, nurturance, guidance and regulation of children and youth including the family, schools, communities, child welfare, and juvenile system. Adopting a life course perspective, the textbook examines the changing legal, social, regulatory, and political landscape of childhood and adolescence within American society with consistent focus on dynamics of race, class, ethnicity, gender, power, and privilege"--
Includes bibliographical references and index.
Keywords: Juvenile delinquency -- Case studies; At-risk youth -- Case studies; Juvenile justice, Administration of -- Case studies